Multiple Organ Dysfunction and Acute Pancreatitis Following Wasp Stings - Shilpakar, Olita; Rajbhandari, Bibek; Karki, Bipin; Bogati, Umesh (Journal of Nepal Health Research Council, 2020)
Wasp stings are common in our part of the world and may cause complications ranging from mild local reactions to fatal anaphylaxis. Severe cases may present with multisystem involvement causing acute kidney injury, hepatic dysfunction, clotting abnormalities, rhabdomyolysis or even death. However, cases with acute pancreatitis as a complication of wasp sting is not usual and have been very rarely reported. We present a case of a fifty-two-year-old lady with the history of multiple wasp stings followed by multiple organ dysfunction and acute pancreatitis with complete recovery following immediate conservative measures.Keywords: Acute kidney injury; multiple organ dysfunction; pancreatitis; wasp; sting